"Aha"ptics: Enjoying an Aesthetic Aha During Haptic Exploration. (January 2019) - Muth, Claudia; Ebert, Sabine; Marković, Slobodan; Carbon, Claus-Christian
Perceptual insight, like recognizing hidden figures, increases the appreciation of visually perceived objects. We examined this Aesthetic Aha paradigm in the haptic domain. Participants were thinking aloud during haptic exploration of 11 visually nonaccessible panels. They explored them again evaluating them on liking, pleasingness, complexity, and interestingness. Afterwards they rated photographs of the panels on the same variables. Haptic pleasingness was predictable by the strength of insight (Aha!) during free exploration and the material feel. Liking was increased when complexity was high in addition. Pleasingness and interest were negatively related to each other but predicted liking in a combined model. Personality and explorative strategies were considered, for example, strength of insight was increased for ambiguity-tolerant people, and people with high need for closure explored more globally. Evaluations of haptic and visual explorations correlated significantly, and in both modalities, complexity correlated more strongly with interest than with liking. Our study transfers the Aesthetic Aha effect to the haptic domain and reveals slight differences in its hedonic quality with a potentially higher relevance of pleasingness. We suggest that revealing a (meaningful) structure during exploration—visually or haptically—can enhance positive affect and interest hereby benefits from an increased level of complexity.